Electrical Resistance Tomographic by Using Current Injection and Magnetic Field Induction - Dudi Darmawan; Deddy Kurniadi; Suprijanto (Journal of Geoscience, Engineering, Environment, and Technology, 2023)
A critical issue in electrical tomography is ill-posed problems due to low sensitivity. In the electric current injection method, the placement of the injection electrode on the object boundary can influence it. This condition causes the reconstruction result of parameter change far away from the boundary to be inferior in quality. Another excitation method is using magnetic field induction proposed to overcome these problems. Each reconstruction image was obtained using two methods with three types of parameter changes, that represented the edge and the center of the object position. Both reconstruction results are merged and further processed to enhance the quality of the image, based on the average value of the resistivity of each element. The results show that the final image reconstruction has a smaller root mean square error (RMSE) than the electric current injection method.